Pengaruh Live Streaming, Content Marketing dan Online Customer Review Terhadap Keputusan Pembelian pada Tiktok Shop (Studi Kasus pada Gen Z Kabupaten Tulungagung) - Sari, Renita; Anasrulloh, Muhammad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to determine the influenceLive Streaming, Content Marketing and Online Customer Review to Purchase Decision at Tiktok Shop (Case Study on Gen Z in Tulungagung Regency. The method used is an associative research method using a quantitative approach. Data was collected through a questionnaire distributed to 96 Gen Z in Tulungagung Regency. The results of the analysis show that there is a significant influence fromLive Streamingon purchasing decisions, with a calculated t value of 2.513 which is greater than the t table (1.987) and a significant value of 0.014 which is smaller than 0.05. In addition, Content Marketing also has a significant negative effect on purchasing decisions, with a calculated t value of 2.671 which is also greater than the t table (1.987) and a significant value of 0.009 which is smaller than 0.05. next Online Customer Revieww hich has no influence on purchasing decisions, with a value of 1.134 which is smaller than (1.987) and a significant value of 2.60 which is greater than 0.05. Simultaneously, these three variables provide a significant contribution to purchasing decisions, with a calculated F value of 4.651 which is much larger than the F table (2.7032) and a significance value of 0.005. The results of the determination coefficient have an influence of 10.3%, while the remaining 89.7% is influenced by other variables outside the study.